PROGRAMA DE ATIVIDADE FÍSICA PARA IDOSOS : PLANEJAMENTO DA PROPOSTA E ANÁLISE DA PERCEPÇÃO DE COORDENADORES DE UNIDADES BÁSICAS DE SAÚDE - ROCHA, CHARLES GUSE DE GODOY (2022)
The increase in life expectancy and the decrease in the birth rate influence the population aging process and, consequently, the increase in the prevalence of senility, chronic conditions or related limitations. The regular practice of physical activity is presented as an important action for the maintenance and improvement of the functional capacity of the elderly. This is what this research is about with a qualitative approach, of the descriptive and explanatory type, with the objective of elaborating a proposal for a physical activity program for the elderly in the context of Primary Health Care and analyzing the perceptions of the coordinators of the Basic Health Units of the municipality of Irati (PR) on this proposal. The study was developed in three stages: the first referred to a systematic literature review; the second consisted of planning a physical activity program for the elderly, aimed at PHC, and the third consisted of presenting the program proposal to UBS coordinators, and analyzing their perceptions, using content analysis as a method, through of the categorical analysis technique. In the systematic review stage, 933 studies were found in the databases and 374 in other sources, and after selection based on the inclusion and exclusion criteria, eight studies were considered eligible for this systematic review. It was verified that 42.8% (n=72) of the 21 items of the RE-AMI model were reported in the studies, with 50% (n=4) being categorized with low quality, and 37.5% (n= 3) moderate quality. The dimensions: reach (75.5%; n=29) and effectiveness (56.2%; n=18) were identified in greater proportion in the studies, when compared to the other dimensions of the RE-AIM. The scientific evidence from the systematic review, from the included studies, showed that most studies were classified as having low or moderate quality. There was a predominance in the reporting of aspects related to internal validity, to the detriment of external validity, focusing more on the presentation of results of interventions at an individual level than on organizational and planning aspects of physical activity programs for the elderly in the context of Health Care. Primary to Health. In the second stage of the research, through the elaboration of the proposal of the physical activity program for the elderly, some important aspects to be considered in the planning were identified: knowing the target population of the program, in a quantitative and qualitative way; assess program development and public health impacts; use instruments and materials that are in line with the local reality; identify and get to know the places and professionals who can work in the program; prioritize multicomponent physical activity sessions, as well as carry out interdisciplinary actions on the topic of healthy habits; identify with the municipal management strategies for the maintenance of the program, even in the face of adversities. In the third stage of the research, it was observed that in the investigated municipality, out of a total of 11 participants, the role of health unit coordinator was delegated to nurses (n=10). The results showed that the perceptions of the coordinators of Basic Health Units about the proposal of a physical activity program for the elderly were: attribution of adjectives connoting approval of the proposal; insertion of the Physical Education professional and development of the program in the health units; perspectives of improvements in the levels of physical and mental health of the elderly participants; potential to promote physical activity for the elderly population attached to the territory of the health unit; dependence on municipal management efforts related to financial resources for the feasibility of implementing programs of this nature; lack of professionals and employees available to work in the program. The contributions from this research may represent a first step towards the implementation of physical activity programs for the elderly in PHC in Irati (PR). A community development concerned with healthy aging is sought, through the promotion of physical activity in actions carried out in the context of PHC, as well as the creation of public policies aimed at strengthening multidisciplinary teams in the municipality's health units.